Numerical Simulation Of Supercritical Flow At Abrupt Expansion Structure With Higher Order Scheme - Lim, Jia Jun (2019)
In the design of hydraulic structures, it is common to deal with the supercritical flow. Abrupt expansion structure represents a type of transition often constructed in manmade hydraulic structure to cater the geometry difference. It is important to cater the design of such transition especially when it involves flow with high velocity. The author developed a two-dimensional depth-averaged model (DA-CIP model) incorporated with Constrained Interpolation Profile (CIP) scheme to increase the accuracy of the numerical model. This study tested the DA-CIP model with verification procedure against analytical solution of dam break flow problem. The author used the DA-CIP model to simulate the supercritical flow phenomena at abrupt expansion channel. The DA-CIP model was capable to reproduce the phenomena mentioned with the flow features such as the formation of demarcation line, zone of constant depth and velocity and the cross waves at the downstream, as well as the reflecting mechanism at the sidewall. The simulated results (without bottom shear stress) was verified with analytical solution and different degree of agreement was observed. This study developed a physical experimental model that reproduced the high-velocity flow at sudden expansion channel for validation purposes. The DA-CIP model shows a high R2 value of 0.9702 for case with Fr=2.45 and 0.9898 for case with Fr =2.50 when validated with experimental data while relatively low R2 value were obtained when using FLOW-3D model.